Alkali-Activation of Non-Wood Biomass Ash: Effects of Ash Characteristics on Concrete Performance - Faris Matalkah; A.G.N.D. Darsanasiri; Saqib Abideen; Anagi Balachadra; Parviz Soroushian (Civil Engineering Journal, 2017)
Combustion of biomass is increasingly practiced for power generation. Unlike coal ash, the combustion ashes of biomass do not offer significant value in Portland cement concrete production. An experimental study was conducted in order to assess the value of the combustion ashes of different non-wood biomass types towards production of alkali activated binders for concrete production. The results indicated that concrete materials with a desired balance of fresh mix workability, set time and compressive strength can be produced used alkali activated non-wood biomass ash binders. Correlations were drawn between the concrete engineering properties and different non-wood biomass ash characteristics. It was found that statistically significant relationships exist between the concrete properties and the non-wood biomass ash degree of crystallinity and solubility. These two ash characteristics were also found to be correlated. It was concluded that the suitability of non-wood biomass ash for use in production of alkali activated concrete can be assessed based on its degree of crystallinity.